Equality of opportunity in the EU - Mišič, Luka (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
The author interprets equality of opportunity as individuals' equal access to primary goods, such as income, wealth, education, health regardless of personal circumstances, natural endowments, and constrains and establishes free movement of EU citizens as persons, not workers or self-employed persons, as a supranational principle of justice. More precisely, the author claims that free movement, regardless of citizens' economic activity or possession of mobile or exportable marketable skills, represents a valid result produced by the supranational application of the fair equality of opportunity principle within the setting of the expending European Union. Primary goods of sufficient value or quality are needed for the individual to develop a rational life plan autonomously and to lead his or her life according to an autonomous conception of the good life with as little adjustment in his or her rational desires as possible. Since the level of adjustment or adaptation varies among the Member States and is, among other, dependent on the level of its social and economic development (e.g. the development of the public services individuals can access), fictitious EU citizens, when placed behind the veil of ignorance, are strongly motivated to neutralise adverse effects of belonging to Member States showcasing a low level of development. From an ex-ante position of the rational future EU citizen, free movement, followed by the second-best result of intra-Member State redistribution, neutralises such adverse effects. Focusing on Principle 3 of the European Pillar of Social Rights, the author endeavours to establish whether the soft-law document allows for or possibly even promotes a reading, which merges the notion of equal opportunities with the idea of free movement, or does it, conversely, adhere to a Member-State-level promotion of equal opportunities, following the idea of market mobility of EU citizens and the current structure of the European Social Model.
Keywords: državljanstvo EU; egalitarni liberalizem; enakost v priložnosti; equality of opportunity; EU citizenship; European Pillar of Social Rights; European social model; evropski socialni model; Evropski steber socialnih pravic; free movement; liberal egalitarianism; socialna varnost; svoboda gibanja